Europium (II) Sulfate EuSO 4 : Synthesis Methods, Crystal and Electronic Structure, Luminescence Properties - Denisenko, Yuriy G.; Sedykh, Alexander E.; Oreshonkov, Aleksandr S.; Molokeev, Maxim S.; Azarapin, Nikita O.; Sal'nikova, Elena I.; Chimitova, Olga D.; Andreev, Oleg V.; Razumkova, Illaria A.; Müller-Buschbaum, Klaus; Justus Liebig University Giessen (My University, 2022)
In the present work, we report on the synthesis of EuSO4 powders by two different methods using EuS as starting material. The compound EuSO4 contains divalent europium and crystallizes in the orthorhombic crystal system, space group Pnma with parameters close to SrSO4. The compound exhibits near isotropic thermal expansion over the temperature range 300–700 K. EuSO4 was examined by Raman, Fourier-transform infrared absorption and luminescence spectroscopy methods. EuSO4 is found to be an indirect bandgap material with a bandgap close to direct electronic transition. The emission lifetime of divalent europium d-f emission in EuSO4 shows an unusual behavior for stoichiometric compounds, as it shortens upon cooling from 1.11(1) μs at room temperature to 0.44(1) μs at 77 K.
Keywords: Europium; Inorganic synthesis; Luminescence; Structure elucidation; Sulfates; ddc:540